Alkaline phosphatase in clinical practice in childhood: Focus on rickets - Cannalire, Giuseppe; Pilloni, Simone; Esposito, Susanna; Biasucci, Giacomo; Di Franco, Anna; Street, Maria Elisabeth (Frontiers in Endocrinology, 2023)
Serum alkaline phosphatase (ALP) and its isoenzymes reflect bone metabolism: ALP increases the ratio of inorganic phosphate to pyrophosphate systemically and facilitates mineralization as well as reduces extracellular pyrophosphate concentration, an inhibitor of mineral formation. On the contrary, low ALP activity is associated with reduction of bone turnover. ALP includes four isoenzymes depending on the site of tissue expression: intestinal ALP, placental ALP, germ cell ALP and tissue nonspecific ALP or liver/bone/kidney ALP. The bone isoenzyme (B-ALP) is involved in bone calcification and is a marker of bone turnover as a result of osteoblastic activity. ALP and its isoenzymes are crucial in the diagnostic process of all the forms of rickets. The most common cause of rickets is vitamin D nutritional deficiency. The aim of this review is to update on the role played by ALP serum concentrations as a relevant marker in the diagnosis and treatment of rickets. Indeed, the diagnosis of rickets is based on its clinical, radiological and laboratory characteristics. An elevated ALP level is one of the markers for the diagnosis of rickets in children, though it is also associated with bone formation process. ALP is also useful for the differentiation between rickets and other disorders that can mimic rickets because of their clinical and laboratory characteristics, and, together with other biochemical markers, is crucial for the differential diagnosis of the different forms of rickets. Age, severity and duration of rickets may also modulate ALP elevation. Finally, ALP measurements are useful in clinical and therapeutic follow-up.